2006
DOI: 10.1159/000089021
|View full text |Cite
|
Sign up to set email alerts
|

Increased Incidence of Sexually Transmitted Infections in Geneva, Switzerland

Abstract: Background: Focal outbreaks of sexually transmitted infections (STIs) such as syphilis and gonorrhoea have been reported in the large cities of Western Europe over the past few years. The aim of our study was to determine whether a similar trend is observed in Geneva and the situation with regard to HIV infection. Methods: We review the incidence of syphilis, gonorrhoea, Chlamydia trachomatis and HIV in Geneva from 1999 to 2004. Results: Figures indicate a steady and sustained increase in the incidence of syph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 44 publications
2
10
0
Order By: Relevance
“…Available surveillance data in Switzerland confirm this trend observed in Zurich and Geneva [1,2]. Notification of syphilis cases almost doubled in the year 2002 and increased to 174% compared to the period of 1998-2001 [1].…”
Section: Introductionsupporting
confidence: 56%
See 1 more Smart Citation
“…Available surveillance data in Switzerland confirm this trend observed in Zurich and Geneva [1,2]. Notification of syphilis cases almost doubled in the year 2002 and increased to 174% compared to the period of 1998-2001 [1].…”
Section: Introductionsupporting
confidence: 56%
“…Briefly, blood was taken from msm who were offered a free, anonymous screening for syphilis in clubs or bars which are known as meeting places for msm in Zurich during 2 After collection the samples were frozen and stored at -30°C. After thawing at 37°C the samples were centrifugated at 3,000 rpm for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…In the Swiss HIV Cohort Study (SHCS), routine screening for syphilis in HIVpositive patients was abandoned at the end of 1998 after an analysis had revealed that screening every 2 years had little impact in the context of the declining incidence at that time (unpublished data). However, the network of Swiss dermatology clinics observed an increase in rates of primary and secondary syphilis beginning in 2001 [23,24]. This observation, paralleled by the international epidemics, led to the reintroduction of systematic annual syphilis serology screening in the SHCS in 2004.…”
Section: Introductionmentioning
confidence: 99%
“…When untreated, the disease progresses through the secondary (disseminated), latent (asymptomatic) and tertiary (recrudescent) stages [1]. After a prominent decline in incidence following the introduction of penicillin as the mainstay of treatment, the disease incidence increased dramatically during the past 20 years [2,3,4,5,6,7]. The increase was initially reported in North America in relation with promiscuous sexual activity associated with the use of crack cocaine [2].…”
Section: Introductionmentioning
confidence: 99%